2001
DOI: 10.1152/ajpheart.2001.280.1.h344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extracellular Mg2+on ROS and Ca2+accumulation during reoxygenation of rat cardiomyocytes

Abstract: The effects of Mg(2+) on reactive oxygen species (ROS) and cell Ca(2+) during reoxygenation of hypoxic rat cardiomyocytes were studied. Oxidation of 2',7'-dichlorodihydrofluorescein (DCDHF) to dichlorofluorescein (DCF) and of dihydroethidium (DHE) to ethidium (ETH) within cells were used as markers for intracellular ROS levels and were determined by flow cytometry. DCDHF/DCF is sensitive to H(2)O(2) and nitric oxide (NO), and DHE/ETH is sensitive to the superoxide anion (O(2)(-).), respectively. Rapidly exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 53 publications
1
33
0
2
Order By: Relevance
“…The investigations by Bolli et al (1) and others (20,21) have shown that reperfusion of previously ischemic myocardium leads to a transient production and release of ROS including H 2 O 2 . In addition, numerous studies have demonstrated that ischemia/reperfusion injury is associated with an inflammatory response characterized by significant infiltration of neutrophils into the myocardium, especially after longer ischemic episodes (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The investigations by Bolli et al (1) and others (20,21) have shown that reperfusion of previously ischemic myocardium leads to a transient production and release of ROS including H 2 O 2 . In addition, numerous studies have demonstrated that ischemia/reperfusion injury is associated with an inflammatory response characterized by significant infiltration of neutrophils into the myocardium, especially after longer ischemic episodes (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular superoxide levels were measured by flow cytometry as the fluorescence of ethidium, which represents the superoxide-sensitive oxidation products of dihydroethidium (Sharikabad et al 2001). Cells were incubated for 10 min with a dihydroethidium probe (2 mM, 0 .…”
Section: Flow Cytometric Determination Of Intracellular Superoxide Lementioning
confidence: 99%
“…4A, ProtA-Nma111p cells showed accumulation of ROS as indicated by dihydroxyethidium (DHE) staining after treatment with H 2 O 2 . DHE reacts with ROS and forms red fluorescent ethidium (Sharikabad et al, 2001). ProtA-Nma111p-NLS1⌬, ProtA-Nma111p-NLS2⌬ and ProtA-Nma111p-NLS1⌬NLS2⌬ cells, by contrast, showed less DHE staining as compared with ProtA-Nma111p cells.…”
Section: Nls Mutants Of Nma111p Lack Proapoptotic Activitymentioning
confidence: 99%